Alumina with specific pore properties
By using alumina with specific porosity and doped elements, the contradiction between thermal stability and density of alumina in the catalyst is solved, and efficient catalyst preparation is achieved.
Patent Information
- Application Number
- CN202080083060.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-11-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-11-25
AI Technical Summary
In the preparation of the motor vehicle pollution control catalyst, there is a contradiction between the thermal stability of alumina and the bulk density. Increased pore volume can improve thermal stability but will lead to a decrease in density and an increase in suspension viscosity.
Alumina with a specific porosity, including additional elements La, Pr or a combination thereof, is used to achieve a balance of high thermal stability and high bulk density by adjusting the proportion of element (E) and pore volume characteristics.
High thermal stability and high bulk density of alumina are achieved, suitable for preparing low viscosity suspensions and improving the effectiveness of catalysts.
Smart Images

Figure GDA0005155924400000221 
Figure GDA0005155924400000222 
Figure HDA0003669758400000011
Abstract
Description
[0001] This patent application claims priority from European Patent Application Nos. 19315154.5 and 19315155.2 filed on November 29, 2019, and the contents of which are incorporated herein by reference in their entirety. In the event of inconsistencies between the text of the present patent application and the text of the French patent application affecting the clarity of terms or expressions, reference should be made only to the present patent application.
[0002] The present invention relates to an aluminum oxide having specific pore characteristics and good thermal stability. The aluminum oxide is also characterized in that the aluminum oxide has a high packing density. Technical Field
[0003] It is a known practice to use aluminum oxide to prepare automotive pollution control catalysts for converting pollutants emitted by gasoline or diesel heat engines. Alumina is used as a carrier for precious metals, especially platinum, palladium and / or rhodium. Alumina can also be combined with other catalyst components, which depend on the catalyst and the intended application (diesel or gasoline pollution control). Among the other common components present in the catalyst, rare earth metal oxides, such as cerium oxide or mixed cerium zirconium oxide, can be mentioned, which are used as materials with oxygen mobility in gasoline engine catalysts (three-way catalysts (TWC) or gasoline particulate filters (GPF)). Alumina can also be combined with zeolites, for example, zeolites are used as hydrocarbon traps for diesel catalysts, or together with zeolites (exchanged with copper and / or iron) are used as catalysts for the catalytic reduction of nitrogen oxides and ammonia (SCR) with ammonia to reduce NO emitted by diesel engines. x .
[0004] Technical issues
[0005] For all these automotive pollution control applications, it is desirable that the thermal stability of the alumina is high, since this enables the effectiveness of the catalyst to be maintained over time, i.e., to maintain a good conversion of gaseous pollutants. The term "thermal stability" means that a high specific surface area is retained after heat treatment at high temperatures. A simple and commonly used method for characterizing the thermal stability of alumina consists in measuring its specific surface area after heat treatment at high temperatures, for example at 1200° C. in air for 5 hours.
[0006] The preparation of automotive pollution control catalysts generally involves depositing or coating alumina-based suspensions on substrates or monoliths. The alumina of the present invention is suitable for preparing suspensions with low viscosity, which enables the preparation of suspensions with a high proportion of alumina. In addition, the high density of the alumina of the present invention facilitates the handling of alumina powders.
[0007] Generally, the thermal stability of alumina is partially related to the pore volume of the alumina. By increasing the pore volume, the thermal stability is generally increased. However, during the process of preparing the catalyst, the increase in pore volume leads to a significant decrease in the density of the alumina and an increase in the viscosity of the alumina suspension.
[0008] To address this problem, it has been observed that the specific porosity of the alumina of the present invention enables both high thermal stability and high packing density to be obtained. Technical Background
[0009] US 4154812 describes a method for preparing aluminum oxide. The method does not include step (e). BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 / 1 shows the diffraction pattern of the aluminum oxide of the present invention (Example 1). It can be observed that the aluminum oxide has characteristic peaks of crystalline aluminum oxide. Summary of the invention
[0011] The present invention relates to said aluminum oxide.
[0012] Thus, the alumina contains the elements Al and O and also an additional element (E), which is La, Pr or the combination La+Pr, the proportion of element (E) possibly being between 0.1% and 6.0% by weight, or even between 0.5% and 6.0% by weight, or even between 1.0% and 6.0% by weight, or even between 2.0% and 6.0% by weight, the proportion being expressed as the weight of this element (E) expressed in oxide form relative to the total weight of the alumina,
[0013] and is characterized by at least one of the following two porosity properties:
[0014] ■First characteristic:
[0015] a pore volume in the range of pores with a size between 5 nm and 100 nm of between 0.60 and 0.85 mL / g, more particularly between 0.60 and 0.80 mL / g; and
[0016] a pore volume within the range of pores with a size between 100 nm and 1000 nm less than or equal to 0.20 mL / g, more particularly less than or equal to 0.15 mL / g, or even less than or equal to 0.10 mL / g, or even less than or equal to 0.05 mL / g;
[0017] and / or
[0018] ■ Second characteristic: After calcination at 1100°C in air for 5 hours:
[0019] - a pore volume in the range of pores with a size between 5 nm and 100 nm of between 0.50 and 0.75 mL / g, more particularly between 0.50 and 0.70 mL / g; and
[0020] a pore volume within the range of pores with a size between 100 nm and 1000 nm less than or equal to 0.20 mL / g, more particularly less than or equal to 0.15 mL / g, or even less than or equal to 0.10 mL / g, or even less than or equal to 0.05 mL / g;
[0021] These pore volumes are determined by mercury porosimetry.
[0022] The alumina may contain sodium and sulfate as well as other impurities.
[0023] The invention also relates to a catalytic composition and also to the use of alumina.
[0024] The present invention relates to a process for preparing aluminum oxide.
[0025] All of these topics are now defined in more detail. DETAILED DESCRIPTION
[0026] In the present patent application, for the sake of continuity of the description, it is specified that, unless otherwise stated, the limit values are comprised within the range of values given. It is also specified that the calcination is carried out in air.
[0027] Furthermore, the concentrations of the solutions or the ratios of the element Al and the element (E) in the alumina are given as weight percentages of the oxide equivalents. The following oxides are thus reserved for the calculation of these concentrations or ratios: Al2O3 for the element Al, La2O3 for the element La and Pr6O3 for the element Pr. 11 For example, an aqueous solution of aluminum sulfate having an aluminum concentration of 2.0% by weight is equivalent to a solution containing 2.0% by weight of Al2O3 equivalent. Similarly, aluminum oxide containing 4.0% lanthanum is equivalent to 4.0% La2O3.
[0028] The term "particle" means an agglomerate formed by primary particles. The particle size is determined by the particle size distribution by volume obtained by a laser particle size analyzer. The particle size distribution is characterized by the parameters D10, D50 and D90. These parameters have the usual meaning in the field of measurement by laser diffraction. Dx therefore represents a value determined according to the particle size distribution by volume, wherein x% of the particles have a size less than or equal to this value Dx. D50 therefore corresponds to the median of the distribution. D90 corresponds to a size wherein 90% of the particles have a size less than D90. D10 corresponds to a size wherein 10% of the particles have a size less than D10. The measurement is usually carried out on a dispersion of particles in water.
[0029] The porosity data were obtained by mercury porosimetry. This technique enables the definition of the pore volume (V) as a function of the pore diameter (D). A Micromeritics Autopore 9520 machine equipped with a powder penetrometer can be used according to the instructions recommended by the manufacturer. The procedure of ASTM D 4284-07 can be followed. From these data, the pore volume (V) within the range of pores with a size between 5 nm and 100 nm can be determined. 5-100nm ), the pore volume (PV) within the range of pores with sizes between 100 nm and 1000 nm 100-1000nm ) and total pore volume (TPV).
[0030] The term "specific surface area" means the BET specific surface area determined by nitrogen adsorption determined by the Brunauer-Emmett-Teller method. This method was described in the journal "The Journal of the American Chemical Society, 60, 309 (1938)". The recommendations of standard ASTM D3663-03 can be followed. Unless otherwise indicated, calcination at a given temperature and a given duration corresponds to calcination in air at a constant temperature stage for the specified duration.
[0031] The aluminum oxide of the present invention is an aluminum oxide containing an additional element (E), which is La, Pr or the combination La+Pr. Therefore, the aluminum oxide is composed of the elements Al, O and €. The element (E) can be especially and advantageously the element La. This type of aluminum oxide containing this element is generally described as doped aluminum oxide. The proportion of element (E) is between 0.1% and 6.0% by weight, or even between 0.5% and 6.0% by weight, the proportion being expressed as the weight of the element (E) expressed in the form of an oxide relative to the total weight of the aluminum oxide. This proportion can be between 1.0% and 6.0% by weight, or even between 2.0% and 6.0% by weight. The element (E) is generally present in the aluminum oxide in the form of an oxide.
[0032] The aluminum oxide of the present invention is characterized by a specific porosity. Therefore, the aluminum oxide has at least one of the following two porosity characteristics:
[0033] First characteristic:
[0034] a pore volume in the range of pores with a size between 5 nm and 100 nm of between 0.60 and 0.85 mL / g, more particularly between 0.60 and 0.80 mL / g; and
[0035] a pore volume within the range of pores with a size between 100 nm and 1000 nm less than or equal to 0.20 mL / g, more particularly less than or equal to 0.15 mL / g, or even less than or equal to 0.10 mL / g, or even less than or equal to 0.05 mL / g;
[0036] Second characteristic : After calcination at 1100°C for 5 hours in air:
[0037] - a pore volume in the range of pores with a size between 5 nm and 100 nm of between 0.50 and 0.75 mL / g, more particularly between 0.50 and 0.70 mL / g; and
[0038] a pore volume within the range of pores with a size between 100 nm and 1000 nm less than or equal to 0.20 mL / g, more particularly less than or equal to 0.15 mL / g, or even less than or equal to 0.10 mL / g, or even less than or equal to 0.05 mL / g;
[0039] Alumina can also be defined by at least one of the following two porosity properties:
[0040] ■First characteristic:
[0041] - a pore volume in the range of pores with a size between 5 nm and 100 nm between 0.60 and 0.85 mL / g; and
[0042] - a pore volume less than or equal to 0.20 mL / g in the range of pores with a size between 100 nm and 1000 nm; and
[0043] and / or
[0044] ■ Second characteristic: After calcination at 1100°C in air for 5 hours:
[0045] - a pore volume in the range of pores with a size between 5 nm and 100 nm between 0.50 and 0.75 mL / g; and
[0046] - a pore volume less than or equal to 0.20 mL / g of pores with a size between 100 nm and 1000 nm.
[0047] The aluminum oxide described in the present patent application may have at least one of the two properties mentioned above, and it should be understood that it may have both properties at the same time.
[0048] In addition, aluminum oxide can have a high specific surface area. Aluminum oxide can have a specific surface area between 100 and 200 m 2 / g, more particularly between 150 and 200 m 2 / g BET specific surface area. This specific surface area can be greater than or equal to 120m 2 / g, preferably greater than or equal to 140m 2 / g. This specific surface area can also be between 100 and 140m 2 / g, or even between 100 and 120 m 2 / g.
[0049] In addition, alumina has high thermal stability. Alumina can have a thermal stability between 45 and 60 m / s after being calcined at 1200 °C in air for 5 hours. 2 / g BET specific surface area between.
[0050] Typically, the alumina has a total pore volume that is generally strictly greater than 1.05 mL / g. This total pore volume may advantageously be at least 1.10 mL / g, or even at least 1.20 mL / g, or even at least 1.30 mL / g, or at least 1.40 mL / g, or at least 1.50 mL / g. This total pore volume generally does not exceed 2.40 mL / g.
[0051] The alumina retains a high total pore volume even after calcination at 1100° C. for 5 hours. Thus, after calcination at 1100° C. for 5 hours, the alumina generally has a total pore volume of at least 0.90 mL / g. This total pore volume is preferably at least 1.00 mL / g, or even at least 1.10 mL / g, or even more advantageously at least 1.20 mL / g. This total pore volume generally does not exceed 1.80 mL / g.
[0052] Alumina can have a value of 0.25 g / cm 3 With 0.55g / cm 3 between 0.40 g / cm 3 With 0.55g / cm 3 The bulk density of alumina powder is equivalent to the weight of a certain amount of powder relative to the volume occupied by the powder:
[0053] Bulk density in g / mL = (mass of powder (g)) / (volume of powder (mL))
[0054] This bulk density can be determined by the following method. First, the volume of a measuring cylinder without a spout of about 25 mL is accurately determined. To this end, the empty measuring cylinder is weighed (tare weight T). Distilled water is then poured into the measuring cylinder up to the edge, but not beyond the edge (no meniscus). The measuring cylinder filled with distilled water is weighed (M). The mass of water contained in the measuring cylinder is therefore:
[0055] E=MT
[0056] The calibrated volume of the cylinder is equal to V 量筒 = E / (density of water at the measuring temperature). For a measuring temperature of 20° C., the density of water is equal to, for example, 0.99983 g / mL.
[0057] Use a funnel to carefully pour the aluminum oxide powder into an empty and dry measuring cylinder until it reaches the edge of the measuring cylinder. Use a spatula to level off the excess powder. The powder must not be compacted or tamped during filling. The measuring cylinder containing the powder is then weighed.
[0058] Bulk density (g / mL) = (mass of the cylinder containing the alumina powder - tare weight T (g)) / (V 量筒 (mL)
[0059] Aluminium oxide may have a D50 between 2.0 μm and 80.0 μm. It may have a D90 less than or equal to 150.0 μm, more particularly less than or equal to 100.0 μm. It may have a D10 greater than or equal to 1.0 μm.
[0060] First embodiment
[0061] According to a first embodiment, the aluminum oxide has a D50 between 2.0 and 15.0 μm, or even between 4.0 and 12.0 μm. The D90 may be between 20.0 and 60.0 μm, or even between 25.0 and 50.0 μm.
[0062] According to the first embodiment, when D50 is between 2.0 and 15.0 μm,
[0063] - Bulk density between 0.25 and 0.40 g / cm 3 between;
[0064] and / or
[0065] - Total pore volume between 1.40 and 2.40 mL / g.
[0066] This total pore volume may advantageously be between 1.50 and 2.40 mL / g.
[0067] Second embodiment
[0068] According to a second embodiment, the aluminum oxide has a D50 between 15.0 and 80.0 μm, or even between 20.0 and 60.0 μm. The D90 may be between 40.0 and 150.0 μm, or even between 50.0 and 100.0 μm.
[0069] According to the second embodiment, when D50 is between 15.0 and 80.0 μm,
[0070] - Bulk density can be between 0.40 and 0.55 g / cm 3 between;
[0071] and / or
[0072] - The total pore volume is between 1.05 (not including this value) and 1.80 mL / g.
[0073] This total pore volume may more advantageously be between 1.20 and 1.80 mL / g.
[0074] The alumina may contain residual sodium. The residual sodium content may be less than or equal to 0.50% by weight, or even less than or equal to 0.15% by weight. The sodium content may be greater than or equal to 50 ppm. This content may be between 50 and 900 ppm, or even between 100 and 800 ppm. This content is expressed as the weight of Na2O relative to the total weight of the alumina. Thus, for an alumina having a residual sodium content of 0.15%, it is considered that there are 0.15 g of Na2O per 100 g of alumina. Methods for determining the sodium content within this concentration range are known to those skilled in the art. For example, inductively coupled plasma spectroscopy techniques may be used.
[0075] The alumina may contain residual sulfate. The residual sulfate content may be less than or equal to 1.00% by weight, or even less than or equal to 0.20% by weight, or even less than or equal to 0.10% by weight. The sulfate content may be greater than or equal to 50 ppm. This content may be between 100 and 1500 ppm, or even between 400 and 1000 ppm. This content is expressed as the weight of sulfate relative to the total weight of the alumina. Thus, for an alumina having a residual sulfate content of 0.50%, it is considered that there are 0.50 g of SO4 per 100 g of alumina. Methods for determining the sulfate content within this concentration range are known to those skilled in the art, such as inductively coupled plasma spectroscopy. Microanalysis techniques may also be used. A microanalysis device of the Horiba EMIA320-V2 type is applicable.
[0076] Alumina may also contain impurities other than sodium and sulfate, for example impurities based on silicon, titanium or iron. The proportion of each impurity is generally less than 0.10% by weight, or even less than 0.05% by weight.
[0077] It will also be noted that the alumina is crystalline. This can be confirmed by X-ray diffraction. The alumina may contain a delta phase, a theta phase, a gamma phase or a mixture of at least two of these phases.
[0078] Specific Alumina
[0079] The aluminum oxide of the present invention may more particularly have at least one of the following two porosity characteristics:
[0080] First characteristic:
[0081] a pore volume in the range of pores with a size between 5 nm and 100 nm of between 0.60 and 0.85 mL / g, more particularly between 0.60 and 0.80 mL / g; and
[0082] - a pore volume less than or equal to 0.05 mL / g within the range of pores with a size between 100 nm and 1000 nm;
[0083] and / or
[0084] Second characteristic : After calcination at 1100°C for 5 hours in air:
[0085] - a pore volume in the range of pores with a size between 5 nm and 100 nm of between 0.50 and 0.75 mL / g, more particularly between 0.50 and 0.70 mL / g; and
[0086] - a pore volume less than or equal to 0.05 mL / g of pores with a size between 100 nm and 1000 nm.
[0087] As mentioned above, this particular aluminum oxide may have at least one of the two properties mentioned above, and it should be understood that it may have both properties at the same time.
[0088] This particular aluminum oxide may also have the following characteristics:
[0089] - Between 150 and 200m 2 / g BET specific surface area; and
[0090] - After calcination at 1100°C for 5 hours in air, the 2 / g BET specific surface area; and
[0091] - at 0.40g / cm 3 With 0.55g / cm 3 The packing density between
[0092] - D50 between 15.0 μm and 80.0 μm; and
[0093] - D90 between 40.0 μm and 150.0 μm.
[0094] The sodium and sulfate contents of this particular alumina are as previously described.
[0095] In addition, the specific alumina may also have a total pore volume characteristic as described above. Thus, the specific alumina generally has a total pore volume that is strictly greater than 1.05 mL / g overall. This total pore volume may advantageously be at least 1.10 mL / g, or even at least 1.20 mL / g, or even at least 1.30 mL / g, or at least 1.40 mL / g, or at least 1.50 mL / g. This total pore volume generally does not exceed 2.40 mL / g.
[0096] This particular alumina retains a high total pore volume even after calcination at 1100° C. for 5 hours. Thus, after calcination at 1100° C. for 5 hours, the alumina generally has a total pore volume of at least 0.90 mL / g. This total pore volume is preferably at least 1.00 mL / g, or even at least 1.10 mL / g, or even more advantageously at least 1.20 mL / g. This total pore volume generally does not exceed 1.80 mL / g.
[0097] Uses of Alumina
[0098] The aluminum oxide of the present invention can be used in the field of pollution control catalysis of gasoline or diesel thermal engine exhaust gases. In this field, a catalytic composition is used, which comprises the aluminum oxide of the present invention and at least one oxide based on cerium and optionally at least one rare earth metal other than cerium. This oxide can be, for example, cerium oxide (generally represented by the formula CeO2), a mixed oxide based on cerium, zirconium and optionally at least one rare earth metal other than cerium. The rare earth metal other than cerium can be selected from the group formed by yttrium, praseodymium and neodymium.
[0099] Preparation method
[0100] The present invention also relates to a method for preparing aluminum oxide, in particular an aluminum oxide as described above, optionally containing an additional element (E) selected from lanthanum, praseodymium or a combination of these two elements, comprising the following steps:
[0101] (a) Into a tank initially containing an acidic aqueous solution at a pH between 0.5 and 4.0, or even between 0.5 and 3.5, the following are introduced under stirring:
[0102] (a1) an aqueous solution of sodium aluminate until a pH of the reaction mixture of between 8.0 and 10.0, or even between 8.5 and 9.5 is obtained;
[0103] (a2) either simultaneously or simultaneously, (i) an aqueous solution of aluminum sulfate and (ii) an aqueous solution of sodium aluminate, until a pH of the reaction mixture of between 6.5 and 10.0, or even between 7.0 and 8.0, or between 8.5 and 9.5 is obtained;
[0104] such that, at the end of step (a), the aluminum concentration of the reaction mixture is between 0.50% and 3.0% by weight;
[0105] (b) subsequently simultaneously introducing an aqueous solution of aluminum sulfate and an aqueous solution of sodium aluminate at a rate such that the average pH of the reaction mixture remains within the target pH range in step (a);
[0106] The temperature of the reaction mixture in steps (a) and (b) is at least 60°C;
[0107] (c) at the end of step (b), optionally adjusting the pH of the reaction mixture to a value between 7.5 and 10.5, or even between 8.0 and 9.0, or between 9.0 and 10.0;
[0108] (d) then filtering the reaction mixture and washing the recovered solid;
[0109] (e) subjecting the dispersion of the solid in water recovered at the end of step (d) to a mechanical or ultrasonic disruption treatment in order to reduce the particle size of the dispersion;
[0110] (f) adding to the dispersion obtained at the end of step (e) at least one salt of the element (E);
[0111] (g) drying the dispersion obtained at the end of step (f);
[0112] (h) The solid obtained from step (g) is then calcined in air.
[0113] Step (a)
[0114] In step (a), the following are introduced under stirring into a tank initially containing an acidic aqueous solution at a pH between 0.5 and 4.0, or even between 0.5 and 3.5:
[0115] (a1) an aqueous solution of sodium aluminate until a pH of the reaction mixture of between 8.0 and 10.0, or even between 8.5 and 9.5 is obtained;
[0116] (a2) either simultaneously or simultaneously, (i) an aqueous solution of aluminum sulfate and (ii) an aqueous solution of sodium aluminate, until a pH of the reaction mixture of between 6.5 and 10.0, or even between 7.0 and 8.0, or between 8.5 and 9.5 is obtained;
[0117] This is such that, at the end of step (a), the aluminium concentration of the reaction mixture is between 0.50 and 3.0% by weight.
[0118] The acidic aqueous solution initially contained in the tank has a pH between 0.5 and 4.0, or even between 0.5 and 3.5. The solution may consist of a dilute aqueous solution of a mineral acid such as sulphuric acid, hydrochloric acid or nitric acid.
[0119] The acidic aqueous solution may also consist of an aqueous solution of an acidic aluminum salt such as aluminum nitrate, aluminum chloride or aluminum sulfate. Preferably, the aluminum concentration of the solution is between 0.01% and 2.0% by weight, or even between 0.01% and 1.0% by weight, or even between 0.10% and 1.0% by weight. Preferably, the acidic aqueous solution is an aqueous aluminum sulfate solution. The solution is prepared by dissolving aluminum sulfate in water or by diluting one or more preformed aqueous solutions in water. The pH of the aqueous solution formed due to the presence of aluminum sulfate is generally between 0.5 and 4.0, or even between 0.5 and 3.5.
[0120] Step (a) is carried out according to both embodiments (a1) or (a2). According to embodiment (a1), the aqueous sodium aluminate solution is introduced under stirring. According to embodiment (a2), (i) the aqueous aluminum sulfate solution and (ii) the aqueous sodium aluminate solution are introduced simultaneously under stirring.
[0121] Preferably, the aqueous sodium aluminate solution does not contain any precipitated alumina. The sodium aluminate preferably has a Na2O / Al2O3 ratio greater than or equal to 1.20, such as between 1.20 and 1.40.
[0122] The aqueous sodium aluminate solution may have an aluminum concentration between 15.0% and 35.0% by weight, more particularly between 15.0% and 30.0% by weight, or even between 20.0% and 30.0% by weight. The aqueous aluminum sulfate solution may have an aluminum concentration between 1.0% and 15.0% by weight, more particularly between 5.0% and 10.0% by weight.
[0123] At the end of step (a), the aluminium concentration of the reaction mixture is between 0.50 and 3.0% by weight.
[0124] In this step (a), the time for introducing the solution or solutions is generally between 2 and 30 min.
[0125] In step (a), the introduction of an aqueous solution of sodium aluminate has the effect of increasing the pH of the reaction mixture.
[0126] In particular for embodiment (a1), the aqueous sodium aluminate solution can be introduced directly into the reaction medium, for example through at least one introduction cannula. In particular for embodiment (a2), the two solutions can be introduced directly into the reaction medium, for example through at least two introduction cannulas. For both embodiments (a1) and (a2), one or more solutions are preferably introduced into a well-stirred region of the reactor, for example into a region close to the stirring rotor, so as to obtain effective mixing of the one or more solutions introduced into the reaction mixture. For embodiment (a2), when the solutions are introduced through at least two introduction cannulas, the injection points through which the two solutions are introduced into the reaction mixture are distributed so that these solutions are effectively diluted in the mixture. Thus, for example, two cannulas can be arranged in the tank so that the injection points of the solutions into the reaction mixture are completely opposite.
[0127] Step (b)
[0128] In step (b), an aqueous solution of aluminum sulfate and an aqueous solution of sodium aluminate are introduced simultaneously, and the introduction rates of these solutions are adjusted so as to keep the average pH of the reaction mixture within the target pH range in step (a). Therefore, the target value of the average pH is:
[0129] - between 8.0 and 10.0, or even between 8.5 and 9.5, in case embodiment (a1) is followed in step (a); or
[0130] - between 6.5 and 10.0, or even between 7.0 and 8.0, or between 8.5 and 9.5, for the case where example (a2) is followed in step (a).
[0131] The term "average pH" means the arithmetic mean of the pH values of the reaction mixture recorded continuously during step (b).
[0132] Preferably, the aqueous sodium aluminate solution is introduced simultaneously with the aqueous aluminum sulfate solution at a flow rate adjusted so that the average pH of the reaction mixture is equal to the target value. During step (b), the flow rate of the aqueous sodium aluminate solution for adjusting the pH may fluctuate.
[0133] The time of introduction of both solutions may be between 10 minutes and 2 hours, or even between 30 minutes and 90 minutes.The flow rate of introduction of one or both solutions may be constant.
[0134] The temperature of the reaction mixture in steps (a) and (b) must be at least 60° C. This temperature may be between 60° C. and 95° C. For this purpose, the solution initially contained in the tank in step (a) may be preheated before the introduction of one or more solutions is started. The solutions introduced into the tank in steps (a) and (b) may also be preheated in advance.
[0135] Step (c)
[0136] In step (c), the pH of the reaction mixture is optionally adjusted to a value between 7.5 and 10.5, or even between 8.0 and 9.0, or between 9.0 and 10.0, by adding a basic or acidic aqueous solution.
[0137] The acidic aqueous solution that can be used to adjust the pH can be composed of an aqueous solution of an inorganic acid such as sulfuric acid, hydrochloric acid or nitric acid. The acidic aqueous solution can also be composed of an aqueous solution of an acidic aluminum salt such as aluminum nitrate, aluminum chloride or aluminum sulfate.
[0138] The alkaline aqueous solution that can be used to adjust the pH can be composed of an aqueous solution of an inorganic base such as sodium hydroxide, potassium hydroxide or ammonia. The alkaline aqueous solution can also be composed of an aqueous solution of an alkaline aluminum salt such as sodium aluminate. Preferably, an aqueous solution of sodium aluminate is used.
[0139] Preferably, the pH is adjusted by:
[0140] (c1) - introducing an aqueous sulfate solution and continuing to introduce an aqueous sodium aluminate solution until the target pH is reached; or alternatively
[0141] (c2) - Introduce aqueous sodium aluminate solution and continue to introduce aqueous aluminum sulfate solution until the target pH is reached.
[0142] According to one embodiment, the introduction of the aqueous solution of aluminum sulfate is stopped and the introduction of the aqueous solution of sodium aluminate is continued until a target pH between 8.0 and 10.5, and preferably between 9.0 and 10.0, is reached. The duration of step (c) may be variable. This duration may be between 5 min and 30 min.
[0143] Step (d)
[0144] In step (d), the reaction mixture is filtered. The reaction mixture is usually in the form of a slurry. The solid recovered on the filter can be washed with water. For this purpose, hot water with a temperature of at least 50° C. can be used.
[0145] Step (e)
[0146] In step (e), the dispersion of the solid recovered in water at the end of step (d) is subjected to mechanical or ultrasonic disruption in order to reduce the particle size of the dispersion. Before grinding, the pH of the dispersion may optionally be adjusted to between 5.0 and 8.0. For this purpose, for example, nitric acid solution may be used.
[0147] Before mechanical or ultrasonic disruption, the D50 of the particles of the dispersion is generally between 10.0 μm and 40.0 μm, or even between 10.0 μm and 30.0 μm. After mechanical or ultrasonic disruption, the D50 of the particles of the solid is preferably between 1.0 μm and 15.0 μm, or even between 2.0 μm and 10.0 μm.
[0148] Mechanical treatment includes applying mechanical stress or shearing force to the dispersion in order to classify the particles. Mechanical treatment can be carried out, for example, by a ball mill, a high pressure homogenizer, or a grinding system comprising a rotor and a stator. On a laboratory scale, a Microcer or Labstar Zeta ball mill can be used, both of which are sold by Netzsch (see: https: / / www.netzsch-grinding.com / fr / produits-solutions / broyage- humide / broyeurs-de-laboratoire-serie-mini / ). A grinding system as described in the examples can be used. In the case of a ball mill, for example, yttrium stabilized zirconia beads can be used. For example, ZetaBeads Plus 0.2 mm balls can be used.
[0149] Ultrasonication, for its part, involves applying sound waves to a dispersion. Sound waves propagating through a liquid medium induce cavitation, which enables the particles to be classified. At laboratory scale, an ultrasonication system with a Sonics Vibracell VC750 generator equipped with a 13 mm probe can be used. The duration and applied power are adjusted so that the target D50 is achieved.
[0150] Mechanical or ultrasonic disruption treatment can be performed in batch mode or continuously.
[0151] Step (f)
[0152] In step (f), at least one salt of element (E) is added. It is also conceivable to add aqueous ammonia solution in this step to raise the pH, preferably to a value between 5.0 and 8.0.
[0153] Step (g)
[0154] In step (g), the dispersion from step (f) is dried, preferably by spraying.
[0155] Spray drying has the advantage of giving particles a controlled size distribution. This drying method also provides good production efficiency. The drying method comprises spraying the dispersion as a droplet mist into a hot gas stream (e.g., a hot air stream) circulating in a chamber. The quality of the spray controls the size distribution of the droplets and, therefore, the size distribution of the dried particles. The spraying can be carried out using any sprayer known per se. There are two main types of spraying devices: turbines and nozzles. With regard to the various spraying techniques that can be implemented in the method of the present invention, reference can be made in particular to Masters' standard manual entitled "Spray-drying" (Second Edition, 1976, published by George Godwin, London). The operating parameters that can be modified by a person skilled in the art are, in particular, as follows: the flow rate and temperature of the dispersion entering the sprayer; the flow rate, pressure, humidity and temperature of the hot gas. The inlet gas temperature is typically between 100°C and 800°C. The outlet gas temperature is typically between 80°C and 150°C.
[0156] The D50 of the powder recovered at the end of step (g) is generally between 2.0 μm and 80.0 μm. This size is related to the size distribution of the droplets leaving the sprayer. The evaporation capacity of the atomizer is generally related to the size of the chamber. Therefore, at laboratory scale (Büchi B 290), the D50 may be between 2.0 and 15.0 μm. At a larger scale, the D50 may be between 15.0 and 80.0 μm.
[0157] Step (h)
[0158] In step (h), the solid obtained from step (g) is calcined in air. The calcination temperature is generally between 500° C. and 1000° C., more particularly between 800° C. and 1000° C. The calcination time is generally between 1 and 10 hours. The calcination conditions given in the examples can be used.
[0159] It is possible to envisage carrying out these two steps (g) and (h) in the same apparatus in which the dispersion obtained from step (f) undergoes a thermal treatment carrying out both drying and calcination.
[0160] Preferably, the alumina recovered at the end of step (h), ie at the end of calcination, generally has a D50 between 2.0 and 80.0 μm. The alumina generally has a D90 less than or equal to 150.0 μm, more particularly less than or equal to 100.0 μm.
[0161] According to a first embodiment, at the end of step (h), D50 may be between 2.0 and 15.0 μm, or even between 4.0 and 12.0 μm. D90 may be between 20.0 and 60.0 μm, or even between 25.0 and 50.0 μm. This embodiment is more likely to be performed when step (f) is performed on a laboratory scale using, for example, a Büchi B 290 nebulizer.
[0162] According to a second embodiment, at the end of step (h), D50 may be between 15.0 and 80.0 μm, or even between 20.0 and 60.0 μm. D90 may be between 40.0 and 150.0 μm, or even between 50.0 and 100.0 μm. This embodiment is more likely to be performed when step (f) is performed on a larger scale.
[0163] The method may also include a final step by which the solid obtained in the previous step is subjected to grinding in order to adjust the particle size of the solid. A knife mill, an air jet mill, a hammer mill, or a ball mill may be used. Preferably, the ground product has a D50 generally between 2.0 μm and 15.0 μm. D90 may be between 20.0 μm and 60.0 μm, or even between 25.0 μm and 50.0 μm.
[0164] The alumina of the present invention is in the form of powder.
[0165] Further details regarding the preparation of the alumina of the present invention are found in the following illustrative examples.
[0166] Examples
[0167] Measurement of specific surface area:
[0168] For the continuity of this specification, the term "specific surface area" means the BET specific surface area determined by nitrogen adsorption according to the standard ASTM D 3663-03 established by the Bruno-Emmett-Teller method described in the journal "The Journal of the American Chemical Society", 60, 309 (1938). The specific surface area is determined automatically using, for example, a Tristar II 3020 machine from Micromeritics according to the instructions recommended by the manufacturer. The sample is preheated at 250° C. for 90 min under vacuum (for example, to a pressure of 50 mmHg). This treatment enables the removal of physically adsorbed volatile substances (such as H2O, etc.) on the surface.
[0169] Porosity Measurement Using Mercury
[0170] The measurements are carried out using a mercury porosimetry machine. In the present case, a Micromeritics Autopore IV 9520 machine equipped with a powder penetrometer can be used, according to the instructions recommended by the manufacturer. The following parameters are used: penetrometer used: 3.2 ml (Micromeritics reference: penetrometer model, No. 8); capillary volume: 0.412 ml; maximum pressure ("head"): 4.68 psi; contact angle: 130°; surface tension of mercury: 485 dynes / cm; density of mercury: 13.5335 g / ml. At the beginning of the measurement, a vacuum of 50 mmHg is applied to the sample for 5 min. The equilibration times are as follows: low pressure range (1.3-30 psi): 20 s - high pressure range (30-60000 psi): 20. Prior to the measurement, the sample is treated at 200° C. for 120 min to remove physically adsorbed volatile substances (such as H2O, etc.) on the surface.
[0171] From this measurement, the pore volume can be deduced.
[0172] Measurement of particle size (D10, D50, D90)
[0173] For particle size measurement a Malvern Mastersizer 2000 or 3000 laser diffraction particle size analyzer was used (further details on this machine are given here: https: / / www.malvernpanalytical.com / fr / products / product-range / mastersizer-range / mastersizer-3000 ). The laser diffraction technique used involves measuring the intensity of light scattered during the passage of a laser beam through a dispersed particle sample. The laser beam passes through the sample and the intensity of the scattered light is measured as a function of angle. The diffraction intensity is then analyzed to calculate the particle size using the Mie scattering theory. This measurement enables the volume-based size distribution to be obtained, from which the parameters D10, D50 and D90 are derived.
[0174] Example 1: Alumina (96% Al2O3-4% La2O3)
[0175] 3200 g of deionized water are placed in a tank stirred by a pitch-blade stirring rotor and equipped with a pH probe located above the liquid, and the water is heated to 75° C. This temperature is maintained during steps (a) to (c). 285 g of an aluminum sulfate solution having a concentration of 8.3% by weight of aluminum oxide (Al2O3) are introduced at a flow rate of 19 g / min through an introduction sleeve close to the stirring rotor. At the end of the introduction, the pH of the raw material is close to 1.5 and the aluminum concentration is 0.7% by weight. The introduction of the aluminum sulfate solution is then stopped.
[0176] Step (a):A sodium aluminate solution having a concentration of 24.9% by weight of aluminum oxide (Al2O3) and a Na2O / Al2O3 molar ratio of 1.27 was introduced through a second introduction sleeve close to the stirring rotor at a flow rate of 14 g solution / min until the pH reached 9.0. The introduction was then stopped. The aluminum concentration of the reaction mixture was then 2.10%.
[0177] In step (b), the introduction of aluminum sulfate solution was started again at a flow rate of 12 g solution / min and simultaneously sodium aluminate solution was introduced into the stirred reactor at a flow rate adjusted to maintain the pH at a value of 9.0. This step lasted 45 minutes.
[0178] In step (c), the introduction of the aluminum sulfate solution was stopped and the addition of the sodium aluminate solution was continued at a flow rate of 5 g solution / min until the pH reached 9.5. The addition of the sodium aluminate solution was then stopped.
[0179] In step (d), the reaction slurry was poured onto a vacuum filter. At the end of the filtration, the filter cake was washed with deionized water at 60°C.
[0180] In step (e), the filter cake is redispersed in deionized water to obtain a dispersion with a concentration of oxide (Al2O3) of about 11% by weight. A nitric acid solution with a concentration of 69% by weight is added to the suspension to obtain a pH close to 6.2. The suspension is passed through a ball mill of the Labstar Zeta brand from the manufacturer NETZSCH. The operating conditions of the grinding are adjusted so as to obtain a D50 of 4.2 microns.
[0181] In step (f), an aqueous solution of lanthanum acetate is prepared with a concentration of about 8% by weight of oxide (La2O3). This solution is added to the suspension obtained from step (e) under stirring, so as to obtain a La2O3 / (La2O3+Al2O3) mass ratio of 4.0%.
[0182] In step (g), the suspension obtained from step (f) is atomized to obtain a dry lanthanum-doped aluminum hydrate powder.
[0183] In step (h), the atomized powder was calcined at 900°C for 2 hours (temperature ramp rate 4°C / min). The mass loss observed during this calcination was 26.1%.
[0184] Example 2: Alumina (98% Al2O3-2% La2O3)
[0185] 157 kg of deionized water are introduced into the same stirred reactor and heated to 85° C. This temperature is maintained during steps (a) to (c). 13.8 kg of aluminum sulfate solution having a concentration of 8.3% by weight of aluminum oxide (Al2O3) are introduced through an introduction cannula close to the stirring rotor at a flow rate of 920 g of solution / min. At the end of the introduction, the pH of the feedstock is close to 2.6 and the aluminum concentration is 0.7% by weight. The introduction of the aluminum sulfate solution is then stopped.
[0186] Step (a): A sodium aluminate solution having a concentration of 24.9% by weight of aluminum oxide (Al2O3) and a Na2O / Al2O3 molar ratio of 1.27 was introduced through a second introduction sleeve close to the stirring rotor at a flow rate of 690 g solution / min until the pH reached 9.0. The introduction was then stopped. The aluminum concentration of the reaction mixture was then 2.10%.
[0187] In step (b), the introduction of aluminum sulfate solution was started again at a flow rate of 570 g solution / min and simultaneously sodium aluminate solution was introduced into the stirred reactor at a flow rate adjusted to maintain the pH at a value of 9.0. This step lasted 45 minutes.
[0188] In step (c), the introduction of the aluminum sulfate solution was stopped and the addition of the sodium aluminate solution was continued at a flow rate of 320 g solution / min until the pH reached 9.5. The addition of the sodium aluminate solution was stopped.
[0189] In step (d), the reaction slurry was poured onto a vacuum filter. At the end of the filtration, the filter cake was washed with deionized water at 65°C.
[0190] In step (e), the filter cake is redispersed in deionized water to obtain a suspension having a concentration of oxide (Al2O3) of about 10% by weight. A nitric acid solution having a concentration of 69% by weight is added to the suspension to obtain a pH close to 6. The suspension is passed through a ball mill of the LME20 brand from the manufacturer NETZSCH. The operating conditions of the milling are adjusted to obtain a D50 of 3.5 microns.
[0191] In step (f), a lanthanum acetate solution with a concentration of about 6.9% by weight of oxide (La2O3) is prepared. This solution is added to the suspension obtained from step (e) under stirring, so as to obtain a La2O3 / (La2O3+Al2O3) mass ratio of 2%.
[0192] In step (g), the suspension obtained from step (f) is atomized to obtain a dry lanthanum-doped aluminum hydrate powder.
[0193] In step (h), the atomized powder was calcined at 940°C for 2 hours (temperature ramp rate 3°C / min). The mass loss observed during this calcination was 25.8%.
[0194] Example 3: Preparation of aluminum oxide containing 4% lanthanum (96% Al2O3-4% La2O3) according to the present invention
[0195] Steps (a) to (e) of Example 2 were repeated. In step (f), a lanthanum acetate solution with a concentration of about 6.9% by weight of oxide (La2O3) was prepared. This solution was added to the suspension obtained from step (e) with stirring, so as to obtain a La2O3 / (La2O3+Al2O3) mass ratio of 4%. An aqueous ammonia solution of 10.0% by weight was then added, so as to obtain a pH of 8.7.
[0196] In step (g), the suspension obtained from step (f) is atomized to obtain a dry lanthanum-doped aluminum hydrate powder.
[0197] In step (h), the atomized powder was calcined at 940°C for 2 hours (temperature ramp rate 3°C / min). The mass loss observed during this calcination was 26.9%.
[0198] Example 4: Alumina (96% Al2O3-4% La2O3)
[0199] 120 kg of deionized water are introduced into the same stirred reactor and heated to 67° C. This temperature is maintained during steps (a) to (c). 1.85 kg of an aluminum sulfate solution having a concentration of 8.3% by weight of aluminum oxide (Al2O3) are introduced through an introduction cannula close to the stirring rotor at a flow rate of 370 g of solution / min. At the end of the introduction, the pH of the feedstock is close to 3.0 and the concentration expressed in oxide equivalents is 0.13% by weight.
[0200] Step (a): The flow rate of the aluminum sulfate solution was increased to 1020 g solution / min, and at the same time, a sodium aluminate solution having a concentration of 24.9% by weight of aluminum oxide (Al2O3) and a Na2O / Al2O3 molar ratio of 1.27 was introduced through a second introduction sleeve near the stirring rotor at a flow rate of 1020 g solution / min until a pH of 7.3 was reached. The aluminum concentration of the reaction mixture was then 1.40%.
[0201] In step (b), aluminum sulfate solution is introduced at a flow rate of 1020 g solution / min and simultaneously sodium aluminate solution is introduced into the stirred reactor at a flow rate adjusted to keep the pH at a value of 7.3. This step lasts 45 minutes.
[0202] In step (c), the introduction of aluminum sulfate solution was stopped and the addition of sodium aluminate solution was continued at a flow rate of 1020 g solution / min until the pH reached 10.3. The addition of sodium aluminate solution was stopped.
[0203] In step (d), the reaction slurry was poured onto a vacuum filter. At the end of the filtration, the filter cake was washed with deionized water at 65°C.
[0204] In step (e), the filter cake is redispersed in deionized water to obtain a suspension having a concentration of oxide (Al2O3) of about 13% by weight. A nitric acid solution having a concentration of 69% by weight is added to the suspension to obtain a pH close to 6.2. The suspension is passed through a ball mill of the LME20 brand from the manufacturer NETZSCH. The operating conditions of the milling are adjusted so as to obtain a D50 of 13.4 microns.
[0205] In step (f), a lanthanum acetate solution with a concentration of about 6.9% by weight of oxide (La2O3) is prepared. This solution is added to the suspension obtained from step (e) under stirring, so as to obtain a La2O3 / (La2O3+Al2O3) mass ratio of 4.0%.
[0206] In step (g), the suspension obtained from step (f) is atomized to obtain a dry lanthanum-doped aluminum hydrate powder.
[0207] In step (h), the atomized powder was calcined at 1035°C for 2 hours (temperature ramp rate 3°C / min). The mass loss observed during this calcination was 33%.
[0208] Example 5: Preparation of aluminum oxide containing 4% lanthanum (96% Al2O3-4% La2O3) according to the present invention
[0209] Steps (a) to (d) in Example 1 were repeated.
[0210] In step (e), the filter cake from step (d) is redispersed in deionized water to obtain a dispersion having an oxide (Al2O3) concentration of about 11% by weight. A nitric acid solution having a concentration of 69% by weight is added to the suspension to obtain a pH close to 6.2. 250 g of the suspension are taken and treated with an ultrasonic crushing probe. The following equipment is used: an ultrasonic crushing system (converter: CV334+13mm probe tip (part number: 630-0220)) with a 750W Sonics Vibracell VC750 generator equipped with a 13mm probe (exchangeable tip). The ultrasonic crushing treatment lasts for 320 seconds. As read on the generator, the energy delivered is 33000 joules. The final temperature of the suspension is 56°C. The suspension is left to cool. At the end of the treatment, the D50 of the suspension is 6.2 microns.
[0211] In step (f), a lanthanum acetate solution with a concentration of about 8% by weight of oxide (La2O3) is prepared. This solution is added to the suspension obtained from step (e) under stirring, so as to obtain a La2O3 / (La2O3+Al2O3) mass ratio of 4.0%.
[0212] In step (g), the suspension obtained from step (f) is atomized to obtain a dry lanthanum-doped aluminum hydrate powder.
[0213] In step (h), the atomized powder was calcined at 900°C for 2 hours (temperature ramp rate 4°C / min). The mass loss observed during this calcination was 26.3%.
[0214] Example 6: Preparation of alumina containing 4% lanthanum (96% Al2O3-4% La2O3) according to the present invention
[0215] Steps (a) to (d) in Example 1 were repeated.
[0216] In step (e), the filter cake is redispersed in deionized water to obtain a dispersion with a concentration of oxide (Al2O3) of about 11% by weight. A nitric acid solution with a concentration of 69% by weight is added to the suspension to obtain a pH close to 6.2. 250 g of this suspension are taken and placed in a ball mill of the Microcer brand from the manufacturer NETZSCH. The operating conditions of the grinding are adjusted so as to obtain a D50 of 3.3 microns.
[0217] In step (f), a lanthanum acetate solution with a concentration of about 8% by weight of oxide (La2O3) is prepared. This solution is added to the suspension obtained from step (e) under stirring, so as to obtain a La2O3 / (La2O3+Al2O3) mass ratio of 4.0%.
[0218] In step (g), the suspension obtained from step (f) is atomized to obtain a dry lanthanum-doped aluminum hydrate powder.
[0219] In step (h), the atomized powder was calcined at 900°C for 2 hours (temperature ramp rate 4°C / min). The mass loss observed during this calcination was 27.4%.
[0220] Table I
[0221]
[0222] Table II
[0223]
Claims
1. Aluminium oxide comprising an additional element (E) which is La, Pr or the combination La+Pr, the proportion of the element (E) being between 0.1% and 6.0% by weight, the proportion being expressed as the weight of the element (E) expressed in the form of oxide relative to the total weight of the aluminium oxide, the aluminium oxide being characterized by at least one of the following two porosity characteristics: ■First characteristic: - a pore volume in the range of pores with a size between 5 nm and 100 nm between 0.60 and 0.85 mL / g; and - a pore volume less than or equal to 0.20 mL / g within the range of pores with a size between 100 nm and 1000 nm; and / or ■ Second characteristic: After calcination at 1100°C in air for 5 hours: - a pore volume in the range of pores with a size between 5 nm and 100 nm between 0.50 and 0.75 mL / g; and - a pore volume less than or equal to 0.20 mL / g within the range of pores with a size between 100 nm and 1000 nm; These pore volumes are determined by mercury porosimetry. The aluminum oxide has a temperature between 45 and 60 m / s after being calcined at 1200°C in air for 5 hours. 2 / g BET specific surface area, or It has a total pore volume of at least 0.90 mL / g after calcination at 1100° C. for 5 hours, as determined using mercury porosimetry.
2. Aluminium oxide according to claim 1, wherein the proportion of the element (E) is between 0.5% and 6.0% by weight.
3. Aluminium oxide according to claim 1, wherein the proportion of the element (E) is between 1.0% and 6.0% by weight.
4. Aluminium oxide according to claim 1, wherein the proportion of the element (E) is between 2.0% and 6.0% by weight.
5. Aluminium oxide doped with an element (E), the element being La, Pr or the combination La+Pr, the element (E) being in a proportion between 0.1% and 6.0% by weight, the proportion being the weight of the element (E) expressed in the form of oxide relative to the total weight of the aluminium oxide, the aluminium oxide being characterised by at least one of the following two porosity characteristics: ■First characteristic: - a pore volume in the range of pores with a size between 5 nm and 100 nm between 0.60 and 0.85 mL / g; and - a pore volume less than or equal to 0.20 mL / g within the range of pores with a size between 100 nm and 1000 nm; and / or ■ Second characteristic: After calcination at 1100°C in air for 5 hours: - a pore volume in the range of pores with a size between 5 nm and 100 nm between 0.50 and 0.75 mL / g; and - a pore volume less than or equal to 0.20 mL / g within the range of pores with a size between 100 nm and 1000 nm; These pore volumes are determined by mercury porosimetry. The aluminum oxide has a temperature between 45 and 60 m / s after being calcined at 1200°C in air for 5 hours. 2 / g BET specific surface area, or It has a total pore volume of at least 0.90 mL / g after calcination at 1100° C. for 5 hours, as determined using mercury porosimetry.
6. Aluminium oxide according to claim 5, wherein the proportion of the element (E) is between 0.5% and 6.0% by weight.
7. Aluminium oxide according to claim 5, wherein the proportion of the element (E) is between 1.0 and 6.0% by weight.
8. Aluminium oxide according to claim 5, wherein the proportion of the element (E) is between 2.0% and 6.0% by weight.
9. Alumina according to claim 1 or 5, having a density between 100 and 200 m 2 / g BET specific surface area between.
10. Alumina according to claim 1 or 5, having a density between 150 and 200 m 2 / g between BET specific surface area.
11. The aluminum oxide according to claim 1 or 5, having a carbon content of 0.25 g / cm 3 With 0.55g / cm 3 The packing density between.
12. The aluminum oxide according to claim 1 or 5, having a carbon content of 0.40 g / cm 3 With 0.55g / cm 3 The packing density between.
13. The alumina of claim 1 or 5 having a total pore volume strictly greater than 1.05 mL / g, as determined using mercury porosimetry techniques.
14. The aluminum oxide according to claim 1 or 5, characterized in that For the first characteristic, the pore volume within the range of pores having a size between 100 nm and 1000 nm is less than or equal to 0.05 mL / g.
15. The aluminum oxide according to claim 1 or 5, characterized in that For the second characteristic, the pore volume within the range of pores with a size between 100 nm and 1000 nm is less than or equal to 0.05 mL / g, the pore volume being determined after calcination at 1100° C. for 5 hours in air.
16. The aluminum oxide according to claim 1 or 5, characterized in that D50 is between 15.0 μm and 80.0 μm.
17. The aluminum oxide according to claim 1 or 5, characterized in that D50 is between 20.0 μm and 60.0 μm.
18. The aluminum oxide according to claim 16, characterized in that In the particle size distribution by volume obtained by a laser particle size analyzer, D90 is between 40.0 μm and 150.0 μm, and D90 indicates a size in which 90% of particles have a size smaller than D90.
19. Alumina as claimed in claim 18, wherein D90 is between 50.0 μm and 100.0 μm.
20. Aluminum oxide according to claim 18 or 19, characterized in that Bulk density between 0.40 and 0.55 g / cm 3 between.
21. Alumina as claimed in claim 1 or 5, having a sodium content less than or equal to 0.50% by weight, the sodium content being expressed as the weight of Na2O relative to the total weight of the alumina.
22. Alumina according to claim 21, wherein the sodium content is less than or equal to 0.15% by weight.
23. The alumina of claim 1 or 5, having a sulfate content less than or equal to 1.00% by weight, the sulfate content being expressed as the weight of SO4 relative to the total weight of the alumina.
24. The alumina of claim 23, wherein the sulfate content is less than or equal to 0.20% by weight.
25. The alumina of claim 23, wherein the sulfate content is less than or equal to 0.10% by weight.
26. The alumina of claim 1 or 5 having the first and the second porosity characteristics.
27. A catalytic composition comprising the aluminium oxide as claimed in claim 1 or 5 and at least one oxide based on cerium and optionally at least one rare earth metal other than cerium.
28. A method for preparing aluminum oxide containing an additional element (E) selected from lanthanum, praseodymium or a combination of these two elements as claimed in claim 1 or 5, the method comprising the following steps: (a) Into a tank initially containing an acidic aqueous solution having a pH between 0.5 and 4.0, the following are introduced under stirring: (a1) an aqueous solution of sodium aluminate until a pH of the reaction mixture between 8.0 and 10.0 is obtained; (a2) either simultaneously or simultaneously, (i) an aqueous solution of aluminum sulfate and (ii) an aqueous solution of sodium aluminate, until a pH of the reaction mixture between 6.5 and 10.0 is obtained; such that, at the end of step (a), the aluminum concentration of the reaction mixture is between 0.50% and 3.0% by weight; (b) subsequently simultaneously introducing an aqueous solution of aluminum sulfate and an aqueous solution of sodium aluminate at a rate such that the average pH of the reaction mixture remains within the target pH range in step (a); The temperature of the reaction mixture in steps (a) and (b) is at least 60°C; (c) at the end of step (b), optionally adjusting the pH of the reaction mixture to a value between 7.5 and 10.5; (d) then filtering the reaction mixture and washing the recovered solid; (e) subjecting the dispersion of the solid in water recovered at the end of step (d) to a mechanical or ultrasonic disruption treatment in order to reduce the particle size of the dispersion; (f) adding to the dispersion obtained at the end of step (e) at least one salt of the element (E); (g) drying the dispersion obtained at the end of step (f); (h) then calcining the solid obtained from step (g) in air.
29. The method of claim 28, wherein in step (a), the acidic aqueous solution has a pH between 0.5 and 3.
5.
30. The method of claim 28, wherein in step (a1 ), a pH between 8.5 and 9.5 is obtained.
31. The method of claim 28, wherein in step (a2), a pH between 7.0 and 8.0 is obtained.
32. The method of claim 28, wherein in step (a2), a pH between 8.5 and 9.5 is obtained.
33. The process of claim 28, wherein in step (c), the pH of the reaction mixture is optionally adjusted to a value between 8.0 and 9.
0.
34. The process of claim 28, wherein in step (c), the pH of the reaction mixture is optionally adjusted to a value between 9.0 and 10.0.
Citation Information
Patent Citations
Process for preparing alumina
US4154812A
Amorphous mesoporous and macroporous alumina with an optimized pore distribution, and process for its preparation
US20170129781A1
Extruded alumina catalyst support having controlled distribution of pore sizes
US4301037A